Geographic and temporal distribution of felt seismicity in Costa Rica (1976-2013) in the historical context of the 30 anniversary (1976-2013) of the National Seismological Network (RSN: UCR-ICE) - Linkimer, Lepolt (2014)
The National Seismological Network of Costa Rica (RSN) was created in 1982 through an agreement between the Central American School of Geology of the University of Costa Rica and the Costa Rican Institute of Electricity. In this paper, we present a short review of the RSN contributions in Seismology to the Journal of Geology of Central America (RGAC) that is expressed in 63 publications. We also analyze the geographic and temporal distribution of 3363 earthquakes reported by the RSN through media reports and RGAC publications during 1976-2013. During the analyzed period the annual average of felt earthquakes in Costa Rica was 90, five 5.0-5.9-magnitude earthquakes were felt on average every year, and one 6.0-6.9-magnitude earthquake were felt every two years. Five earthquakes had a magnitude greater than 7.0 including the 1991 Limón (7.7 Mw) and 2012 Samara (7.6 Mw) earthquakes. The majority of felt earthquakes (83,7%) had depths of less than 30 km. The seismogenic sources with the greatest energy release were the shallow processes related to the subduction of the Cocos Plate (54.5%) and the North Panama Deformed Belt (38,7%)